The effect of explicit vs. implicit instruction on mastering the speech act of thanking among Iranian male and female EFL learners - Mehdi Ghaedrahmat; Parviz Alavinia; Reza Biria (Universidad de La Sabana, 2016)
This pragmatic study investigated the speech act of thanking as used by non-native speakers of English. The study was an attempt to find whether the pragmatic awareness of Iranian EFL learners could be improved through explicit instruction of the structure of the speech act of "Thanking". In fact, this study aimed to find out if there was a significant difference between the performances of EFL learners in using the speech act of thanking when they were taught through explicit instruction of speech acts compared with implicit instruction. To this end, 30 Iranian intermediate EFL learners at Pars language institute were chosen, and they were classified as experimental and control group. The researcher adopted a discourse completion test (DCT) to gather the necessary data. The results showed that those learners who were taught explicitly outperformed those to whom implicit instruction was used.   doi: 10.5294/laclil.2016.9.2.7